2010
DOI: 10.1021/jp107991a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of thetranscisPhotoisomerizations of Azobenzene and a Bridged Azobenzene

Abstract: Using density-functional-based molecular dynamics simulations, we have performed comparative studies of the trans-cis isomerizations of azobenzene and bridged azobenzene (B-Ab) 5,6-dihydrodibenzo[c,g][1,2]diazocine induced by nπ* electronic excitation. The quantum yields found in our calculations, 45% for the bridged azobenzene versus 25% for azobenzene, are consistent with the experiment. Both isomerization processes involve two steps: (1) Starting from the trans structure, each molecule moves on its S(1) exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 44 publications
(91 reference statements)
7
38
2
1
Order By: Relevance
“…These photoisomerization processes take place in the picosecond scale and the detailed mechanisms for these transitions have been under debate. 50,51 In this third example, we have used Eq. (18) to calculate the NACV, d α ij , between the HOMO and LUMO KS states for the azobenzene molecule along a pre-selected path between the cis-and trans-conformations.…”
Section: Azobenzenementioning
confidence: 99%
“…These photoisomerization processes take place in the picosecond scale and the detailed mechanisms for these transitions have been under debate. 50,51 In this third example, we have used Eq. (18) to calculate the NACV, d α ij , between the HOMO and LUMO KS states for the azobenzene molecule along a pre-selected path between the cis-and trans-conformations.…”
Section: Azobenzenementioning
confidence: 99%
“…Previous dynamics simulations [19][20][21] demonstrated that one minimum-energy CI plays an important part in nonadiabatic transitions between the two states involved in transcis photodynamics processes. However, in this work, CI 1 and CI 2 were found to be responsible for nonadiabatic transitions during 1E-1Z photoisomerization.…”
Section: B Molecular Dynamics Simulations 1 1e-1z Photoisomerizatiomentioning
confidence: 99%
“…18 Combining an AM1 floating-occupation configuration interaction technique (FOCI-AM1) with Tully's fewest switches surface hopping method, 23 a recent dynamics simulation 19 indicated that trans-cis and cis-trans photoisomerization reactions proceed through two different minimum-energy conical intersections (CIs), with the dynamics starting from the cis isomer following a barrierless path with steep gradients and the dynamics starting from the trans isomer encountering a sizeable barrier in the ground state. In comparative studies of the trans-cis isomerizations of azobenzene and its bridged form by Jiang et al, 20 one minimum-energy CI is found to exist in both isomerization processes, and twisting of the two phenyl rings in bridged azobenzene around their N-C bonds is hindered by the presence of the bridge structure. Additionally, for both cis-trans and trans-cis photoisomerization processes simulated at the density-functional-based tight-binding level, 21 one minimum-energy CI between the ground state (S 0 ) and S 1 state was confirmed to act as the S 1 -S 0 decay funnel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent dynamics simulation employing the AM1 floating-occupation configuration-interaction technique (FOCI-AM1) with Tully's fewest switches surface hopping approach [28] suggested that while the dynamics starting from the Z isomer followed a barrierless path with steep gradients, the dynamics starting from the E isomer proceed through a different conical intersection surrounded by a rather flat potential energy landscape and then encounter a sizeable barrier in the electronic ground state. Density-functional-based semiclassical electron-radiation-ion dynamics simulations (SERID) [29] were employed to compare the trans-cis isomerization of azobenzene and Br-AB by Jiang et al [30] which showed that the bridging part of the molecule slowed the twisting of the two phenyl rings about the CN bonds during the isomerization process, as a result, the time scale for the complete trans-cis isomerization of the Br-AB was approximately the same as in azobenzene. A combination of CASPT2// CASSCF calculation with semiclassical DFTB dynamics simulation [31] revealed that formation of the trans product occurred as the downhill motion on the S 0 surface, while the cis formation needed to overcome small barriers on the pathways of the azo-moiety isomerization and rotation of the phenyl ring around the C-N-N bond.…”
Section: Introductionmentioning
confidence: 99%